Reflect Action Methods - ActionAid (2009)
Reflect is an innovative approach to adult learning and social change, which fuses the theories of Brazilian educator Paulo Freire with part icipatory methodologies. It was developed in the 1990s through pilot p rojects in Bangladesh, Uganda and El Salvador and is now used by over 500 organisations in over 70 countries worldwide. Organisations workin g with Reflect won UNESCO literacy prizes in 2003, 2005, 2007, 2008 an d 2010. This site is aimed at Reflect practitioners and others who wan t to know more about the approach. We want it to be truly interactive and the more stories, graphics and photos are submitted, the better th e site will be. Please add your comments to tell us about the work you are doing with Reflect and join the discussion forum to share your id eas and experiences of working with the approach.